2020
DOI: 10.2166/wh.2020.147
|View full text |Cite
|
Sign up to set email alerts
|

Human water contact patterns in active schistosomiasis endemic areas

Abstract: One major risk factor common to individuals in schistosomiasis endemic areas is water contact patterns. Effort to determine the dynamics in water contact patterns in different regions needs utmost attention in order to suggest better control strategy for schistosome infection. Quantitative observations on human water contact activities were recorded in Yewa North Local Government Area of Ogun State for a period of two years. Frequency and duration of observed water contact activities were recorded. Males had t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…[37][38][39][40][41][42] A study in Benin showed that males had significantly higher frequency of water contact than females. 46 Hence, it is expected that schistosome infection could be higher in males compared to females in the study areas. Furthermore, prevalence of schistosomiasis had been found to be higher in males than in females.…”
Section: Discussionmentioning
confidence: 93%
“…[37][38][39][40][41][42] A study in Benin showed that males had significantly higher frequency of water contact than females. 46 Hence, it is expected that schistosome infection could be higher in males compared to females in the study areas. Furthermore, prevalence of schistosomiasis had been found to be higher in males than in females.…”
Section: Discussionmentioning
confidence: 93%
“…However, the rate of water contacts declined after the age of 40. Majority of the respondents in Similarly, Oso and Odaibo [18] observed an agerelated water-contact patterns with frequency of exposure to infested water reducing with old age. It could also be due to the development of immunity in the old people who may have contracted the disease in their young age.…”
Section: Water Contacts and Perceptionsmentioning
confidence: 95%
“…The subjects from which the study participants were drawn were observed for the environmental contamination with faeces or urine close to the perimeter of the water body, for 4 hrs between 11am and 3pm every day for 3 days. This observation period was believed to be the peak period of WCAs in rural endemic settings and, when the risk of schistosomiasis transmission is highest [11,18]. Afterward, the assessment of riverside contamination was confirmed from the respondents during the questionnaire survey.…”
Section: Questionnaire Surveymentioning
confidence: 99%
“…There are two major forms of schistosomiasis, urogenital schistosomiasis caused by Schistosoma haematobium, and intestinal schistosomiasis, caused by S. mansoni, that are commonly reported in Nigeria. Urogenital schistosomiasis is most widely reported in Nigeria, affecting individuals living in most rural, underprivileged urban or peri-urban settings with limited access to clean water, inadequate sanitation, and hygiene services [3][4][5]. The disease is also commonly found in fishing and agricultural dominant communities where direct interactions with water increase the risk of contracting the disease [6,7].…”
Section: Introductionmentioning
confidence: 99%